Evaluation of the impact of successive acaricide treatments on resistance evolution in Rhipicephalus microplus populations: Monodrugs versus drug combinations - Sarli, Macarena (2023)
The aim of this work was to comparatively evaluate the evolution of resistance in Rhipicephalus microplus tick populations exposed to successive treatments with monodrug-based formulations and combinations of them in the same commercial formulation. Thirty-six heifers, naturally infested with R. microplus, were divided into three groups (G) and subjected to three successive treatments, on days 0 (Nov-2021), 43 (Jan-2022) and 78 (Feb-2022), with the following formulations: I) ivermectin 3.15% (Ivomec Gold®) (GI), II) fipronil 1% (Ectoline®) (GII) and III) a combination of fipronil 2% and ivermectin 1% (Vaquero®) (GIII). From Nov-2021 to Dec-2022, counts of R. microplus were periodically performed to evaluate the tick infestation. Engorged females were collected at the beginning and end of the trial to determine the evolution of tick resistance to ivermectin and fipronil by in vitro bioassays. At the end of trial, GII and GIII had higher tick counts (39.18 ± 11.88 and 38.33 ± 14.31, respectively) than group I (5.11 ± 6.24) (P<0.05). The in vitro results shows that the resistance ratio (RR50) values after the treatments were higher for fipronil (5.584 and 5.649 for GII and GIII, respectively) than for ivermectin (1.165 and 1.088 for GI and GIII, respectively). In the group treated with the combination (GIII), the RR50 increased for both drugs simultaneously. These results suggest that the successive use of drug combinations could exacerbate the problem of multi-resistance of R. microplus to chemical acaricides.